Unleashing Creative Potential: The Impact of Self-Organized Learning Environments (SOLE) on Fifth Grade Students' Creative Thinking Skills - Selvina; Meita Fitrianawati; Afdol Awae (Journal of Pedagogy and Education Science, 2023)
Education is a process of educating the nation's life and improving the quality in humans for moral improvement and intellectual training. This study aims to determine the effect of self-organized learning environment (SOLE) on the creative thinking ability of fifth grade students. This type of research is a quasi-experimental research with the non-equivalent control group research design. The samples selected were fifth grade students. The research instrument is a test of creative thinking skills and inventory. The data analysis used were normality test, homogeneity test, and hypothesis testing using independent sample t-test and paired sample t-test. The results showed that the level of creative thinking ability of the experimental class was proven through activity through analysis of the paired sample t-test hypothesis test tcount 10,187 > ttable 2,100 which means that SOLE has an effect on the creative thinking. Based on the research results, there are the effect of SOLE on the creative thinking skills of fifth grade students.